2013
DOI: 10.1055/s-0033-1343887
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in Nephrotic Syndrome

Abstract: Nephrotic syndrome (NS) is characterized by heavy proteinuria, edema, hypoalbuminemia, and hyperlipidemia and the most frequent causes are glomerular diseases. An uncommon presentation is iatrogenic NS, an adverse effect of some drugs administration. In the clinical course of NS, a typical feature is dysregulated coagulation state, promoted by the breakdown of permselectivity barrier of the glomerular capillary wall, resulting in the leakage of high-molecular-mass proteins, at least the size of albumin. This h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…Interestingly, there have been reports of venous TE being not just limited to severe CKD, but also CKD Stages 1 and 2, and CKD Stage 3 in the presence of albuminuria [ 5 ]. There is a suggestion that the risk of venous TE is more related to albuminuria than to impaired glomerular filtration rate (GFR), reflecting the predominance of this complication in nephrotic syndrome patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there have been reports of venous TE being not just limited to severe CKD, but also CKD Stages 1 and 2, and CKD Stage 3 in the presence of albuminuria [ 5 ]. There is a suggestion that the risk of venous TE is more related to albuminuria than to impaired glomerular filtration rate (GFR), reflecting the predominance of this complication in nephrotic syndrome patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recognized risk factors for thrombosis in children are cancer, surgery, central venous catheters, thrombophilia abnormalities, local compression of the veins and systemic diseases [ 3 , 4 ]. Among the latter nephrotic syndrome is characterized by coagulation impairment, due to the loss of the main circulating natural anticoagulant proteins of relatively low molecular weight, i.e., antithrombin and protein S [ 5 ]. Conflicting data are available on plasma levels of protein C, another naturally occurring anticoagulant protein, in patients with nephrotic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that in patients with nephrotic syndrome not only secondary but also primary hemostasis is impaired. Thrombocytosis is common, and an increased platelet reactivity, the presence of circulating platelets exposing the procoagulant phosphatidylserine and an increased expression of activated glycoprotein IIb-IIIa on the platelet surface have been reported [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[7] In the absence of other indications, patients who achieve remission of NS should have anticoagulation for the next 6 months; even in the clinical course of NS, it is particularly difficult to achieve the goal of prefixed international normalized ratio with oral anticoagulants because of the low levels of albumin. [8]…”
mentioning
confidence: 99%
“…In fact, these agents have high risk of bleeding as a most important complication and require careful administration, especially in patients with NS. [8]…”
mentioning
confidence: 99%